Abnormal cerebellar volume and corticocerebellar dysfunction in early manifest Huntington’s disease - Wolf, Robert Christian; Thomann, Philipp; Sambataro, Fabio; Wolf, Nadine D.; Vasic, Nenad; Landwehrmeyer, Bernhard; Süßmuth, Sigurd; Orth, Michael (Journal of neurology, 2015)
Evidence from animal models and neuropathological data has revealed cerebellar pathology in Huntington’s disease (HD). The extent of cerebellar dysfunction in preclinical stages and in early manifest HD is unclear. In this study, using MRI we investigated cerebellar changes in preclinical (preHD) and early manifest HD individuals. High-resolution structural MRI data at 3 Tesla were obtained from two independent preHD samples (n = 20/25 participants), from two independent cohorts of healthy controls (n = 20/24 participants) and from patients with early manifest HD (n = 20 participants). Resting-state functional MRI data were acquired from 20 healthy controls and 20 HD patients. Cerebellar volume was investigated using cerebellum-optimized voxel-based analysis methods. Corticocerebellar connectivity at rest was investigated by means of seed-region correlations. In both preHD samples, between-group analyses revealed no change of cerebellar volume. In contrast, early manifest HD patients exhibited lower right cerebellar lobule VIIa volume (p < 0.05 cluster-corrected). Within the control group regions functionally coupled to right cerebellar lobule VII comprised bilateral cerebellar regions, right prefrontal and cingulate areas, whereas within manifest HD, functional coupling was found in paracentral, lingual and inferior frontal areas. Paracentral connectivity strength in patients was associated with disease burden and motor symptoms. These data suggest intact cerebellar volume in preHD. In contrast, early manifest HD patients exhibit atrophy of specific cerebellar subregions and abnormal corticocerebellar functional coupling. In early HD, the association between paracentral lobule function and clinical parameters suggests that corticocerebellar connectivity strength is related to the evolution of HD biology and the severity of HD motor signs.
Gesehen am 03.07.2020